Infant with Groin Swelling - Nisha Polavarapu; Brendan Kilbane (Clinical Practice and Cases in Emergency Medicine, 2022)
Case Presentation: A 21-day-old female presented to the pediatric emergency department with swelling of the left groin. Physical examination revealed a soft, nontender abdomen and a two-centimeter firm and fixed mass on the left aspect of her mons pubis. Point-of-care ultrasound revealed a left inguinal hernia with incarcerated ovary. Discussion: Inguinal hernias are common in the pediatric population. In female patients, particularly those less than one year old, inguinal hernias most frequently contain an ovary rather than bowel; so they require careful evaluation to protect future reproductive function.